A Study on Indigenous Plants as Source of Anticancer Agents: An Ethnomedicinal Approach - Prakash, Sadguru; Upadhyay, Sushil Kumar (Asian Journal of Biological and Life Sciences)
Traditional medicine plays an important role in health care provision in the developing countries. In India, there is no documented information of ethnomedicinal knowledge regarding anticancer properties of indigenous plants. Yet, some traditional healers of eastern U.P. claim that they have been treating cancer like symptoms using herbal remedies. The aim of the present investigation was to document the indigenous medicinal plants traditionally used to treat cancer like symptoms in thirteen districts of Uttar Pradesh (U.P.), India. Traditional healers of six tribal communities inhabited in thirteen districts were interviewed using questionnaires and field visits were also carried out to collect claimed plants for identification purpose during the month of April 2019 to March 2020. In the present study, total 31 plant species belonging to 24 families were used by the tribal communities to treat seven types of cancers. Leaves were the most important part to be used in the treatment of cancers. The information suggests that tribal traditions may have much to contribute to the therapeutic armamentarium. Therefore, authors wish to propose the urgent need of conservation and management of the traditional knowledge of indigenous medicinal plants as potential anticancer agents of future.
Keywords: Anticancer agents; Ayurveda; Cancer therapy; ethnomedicine; Herbal remedies; Indigenous plants